Recommendations and practices for holistic chronic obstructive pulmonary disease (COPD) assessment and optimal referral patterns in emergency department presentations: a scoping review protocol. Issue 8 (21st August 2019) - Moloney, Clint; Sneath, Emily; Phillips, Tania; Issac, Hancy; Beccaria, Gavin; Mullens, Amy
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is a common respiratory condition that causes persistent respiratory symptoms and decline in lung function over many years. This chronic disease significantly affects health-related quality of life and is known to contribute to frequent emergency department (ED) presentations. Multidimensional management of these patients, including interconnecting health disciplinarians will allow holistic care provision in the ED. The purpose of this scoping review is to synthesise current evidence on holistic management and assessment, and referral practices stemming from acute COPD presentation in the ED. Specifically, to determine: (1) What are the known causal factors associated with COPD ED presentations and (2) Is there an identified connection with appropriate healthcare professional assessment within ED presentations and reported referral pathways? Methods and analysis: The iterative stages of the Arskey and O'Malley, and Levac advanced scoping review framework informs this review. Using published and unpublished studies in English, a three-tiered search strategy will be applied. After duplicates are removed, screen 1 (title and abstract) and screen 2 (full-text) will be conducted by two independent reviewers to determine eligibility of articles. Disputes will be settled through discussion or by using a third reviewer. A data collection tool developed by the authors will inform the data extraction process. Schematic tabular format of results with a narrative summary will depict how the results link with the scoping review objectives. Categorisation of results will be narrowed down as key conceptual findings and will align with the strategic intent of this review. Ethics and dissemination: Ethics approval was not required for this study. A multidisciplinary team of authors will participate in dissemination activities (publications, reports, conference presentations, framework development).